A new species of Scolytus Geoffroy (Coleoptera, Curculionidae, Scolytinae) from Yunnan, China - Cao, Yufeng; Yu, Guangyu; Petrov, Alexander V.; Li, You; Li, Ting; Tarno, Hagus; Cao, Guanghong; Xu, Ye; Wang, Jianguo (Zootaxa, 2023)
Scolytus unicornis, a new species of Scolytus Geoffroy from Yunnan, China, is described and illustrated. Three DNA barcoding sequences (COI, 28S, CAD) of this species are provided. The new species is distinguished from other Asian Scolytus species by the longitudinal wrinkles on the frons only in the area below the eyes, a large median spine situated in the middle of the ventrite 2 base, and female frons with a slightly raised blunt tubercle above the epistoma.